STEREOTYPE DALAM ETNISITAS DAN IDENTITAS DI INDONESIA - M Taufiq Ridho (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA, 2014)
This paper discusses about the fundamental cause of conflict in ethnicity and identity: stereotype and prejudice. The writer uses the perspective of Jurgen Habermas’s theory of rational discourse and communicative action to analyse the phsycological problem, and to find it’s implication to political action and system of law in the multicultural society. The basic concept here is Lebenswelt, an ideal living society with natural elements of life and no discrimination and ideological domination. Stereotype and prejudice action is an epistemological and phsycological problem of society. So, open discourse and rational dialogue are always needed to build an ethical and just democratic society.